Remediation of Black and Odorous Water using a Slow-release Composite Agent Containing CaO2, Zeolite, and Polymeric Ferric Sulfate: Effects on Water Quality and Chlorella Growth - Jinhai Li; Defu Xu; Yafei Xun; Ying Zhuang; Meiling Guan; Alan Howard (Water, Air, & Soil Pollution, 2026)

Evaluation of Rice Yield Attributes, Loach Muscle Quality, and Soil Biochemical Composition Under Rice–Loach Coculture System - Chuanqi Yu; Wenlu Zhu; Wenjun Wang; Wenqiang Xu; Yu Liu; Xingtian Cai; Yanfa Xu; Defu Yang; Zhuqing Yang; Zirui Wang; Qiubai Zhou; Haohua He (Fishes, 2026)
This study aimed to evaluate rice yield attributes, loach Paramisgurnus dabryanus muscle quality, and soil biochemical composition under rice monoculture (RM), rice–loach coculture (RLC), and loach monoculture (LM). This trial was conducted for 90 days, and then rice, fish muscle and soil were obtained for analyses. The results showed that there were no significant differences in rice yield attributes between the rice–loach coculture (RLC) and rice monoculture (RM) groups. However, rice–loach coculture (RLC) improved muscle quality-related parameters, including increased hardness and springiness of loach muscle. Meanwhile, muscle metabolomic analysis showed that all the differentially expressed metabolites (DEMs) in the significantly enriched pathways of lysine degradation and lysine biosynthesis were up-regulated in the rice–loach coculture (RLC) group compared with the loach monoculture (LM) group. Furthermore, the rice–loach coculture (RLC) improved soil physicochemical properties, including an increase in microbial biomass nitrogen (MBN) content and activities of soil N-acquiring enzymes (NAG and LAP). Moreover, soil microbiome analysis showed that the abundance of Candidatus Koribacter versatilis, Acidobacteria bacterium WX27 and Pseudolabrys taiwanensis was significantly increased in the rice monoculture (RM) and rice–loach coculture (RLC) groups compared with the loach monoculture (LM) group. Pairwise Spearman’s correlation analysis of the top 30 soil microbial species and soil physicochemical properties indicated that Terrimonas sp. H1YJ31 showed a highly significant positive correlation with the soil N-acquiring enzymes (N-acetylglucosaminidase, NAG; leucine aminopeptidase, LAP) and a soil C-acquiring enzyme (exo-β-1,4-glucanase C1), whereas Gaiella occulta, Methyloceanibacter marginalis and Anaerohalosphaera lusitana had a highly significant negative correlation with S-NAG, S-LAP and S-C1. In short, the improved fish muscle quality and soil biochemical composition were ascribed to the increased hardness and springiness of loach muscle and the abundance of soil Terrimonas sp. H1YJ31.

Valorization of illite-bearing mine tailings in LC3 binders enabled by CO2-Mineralized steel slag - Yuming Huo; Haiyong Hu; Yulong Jiang; Defu Zhu; Zekun Xu (Sustainable Chemistry and Pharmacy, 2026)

Zinc-reinforced sandwich-structured nano-magnesium oxide composite collagen barrier membrane for promoting bone regeneration - Hong Du; Shasha Lei; Jianhui Wu; Yiruo He; Lun Yuan; Liming Ge; Changdao Mu; Zhilang Xu; Defu Li (Chemical Engineering Journal, 2026)

Full-scale experimental study of flame behavior and thermal distribution in utility tunnel fires - Xiaojiang Liu; Zhao-Dong Xu; Jun Dai; Jiayu Che; Zhong-Wei Hu; Defu Che (Tunnelling and Underground Space Technology, 2026)

Manipulation of autophagy regulates mitochondrial homeostasis and early embryo development of cryopreserved porcine oocytes - Jiehuan Xu; Mengqian He; Jun Gao; Lingwei Sun; Caifeng Wu; Shushan Zhang; Defu Zhang; Jianjun Dai (Animal Reproduction Science, 2026)

Acid-triggered degradation of a silicon-based nanopesticide activates SA-dependent conifer defense against Dioryctria sylvestrella - Zheng Wang; Antong Ma; Jiaxing Fang; Xiaoqi Xu; Wei Gan; Jiayue Liu; Fu Liu; Sufang Zhang; Defu Chi; Dafeng Chen; Yapei Wang; Xiangbo Kong (Pesticide Biochemistry and Physiology, 2026)

Autotrophic denitrification filter prepared using gasification coarse slag and pyrite: Physicochemical characteristics and performance removal of nitrogen - Shuhan Yang; Defu Xu; Jing Su; Zhengxuan Li; Alan Howard (International Biodeterioration & Biodegradation, 2026)

Preliminary analysis of a slow-moving high-locality landslide in the Zagunao River Basin, Sichuan Province, China - Shengsen Zhou; Weile Li; Huiyan Lu; Zhou Xu; Wenlong Yu; Shanmiao Xu; Pan Zhang; Chunhao Wei; Yusen Li; Defu Wang; Weiwei Zhan; Qiang Xu (Bulletin of Engineering Geology and the Environment, 2025)

Remote sensing monitoring of changes in land cover in the Tiefa Coalfield under the joint impact of extreme climate and mining activities (1984–2023) - Baodong Ma; Ting Kang; Renfeng Gao; Defu Che; Zhongyin Xu (Environment, Development and Sustainability, 2025)

Characterization of volatile flavour compounds and characteristic flavour precursors in poultry eggs based on multi-omics and machine learning - Hongqiang Li; Xiangmin Zhao; Xiaoming Li; Jing Liang; Shizhen Qin; Jinlu Li; Aiwen Zhang; Linna Xu; Defu Tang; Fuwei Li (Food Chemistry, 2025)

Land cover types and depth regulate carbon and nitrogen cycle functional genes in permafrost regions on the Qinghai-Tibet Plateau - Xiaoying Fan; Xiaodong Wu; Dejincuo Ma; Tonghua Wu; Guimin Liu; Haiyan Xu; Defu Zou; Guojie Hu; Yadong Liu; Xianhua Wei; Xuchun Yan; Yongxiang Liu; et al. (Plant and Soil, 2025)

Efforts toward achieving the goal of ending AIDS by 2030: from antiretroviral drugs to HIV vaccine and cure research - Peng Xu; Defu Yuan; Christiane Moog; Bin Su (Science China Life Sciences, 2025)

Simulation study on seasonal recovery of waste heat and water resources in flue gas and slurry after WFGD - Gaofeng Fan; Xinyue Gao; Chang’an Wang; Yujie Hou; Jinming Zhang; Jie Xu; Defu Che (Process Safety and Environmental Protection, 2025)

Preparation of a slow-release fertilizer from MgO-modified biochar and struvite and its capacity for cadmium passivation - Zanmei Chen; Defu Xu; Die Wu; Tingtian Lu; Alan Howard (Journal of Environmental Chemical Engineering, 2024)

Multisource remote sensing monitoring and analyzing for land subsidence and crop growth in a coal mining area under different rainfall conditions - Baodong Ma; Renfeng Gao; Defu Che; Zhongyin Xu; Duo Wang; Yanen Sun (Environmental Development, 2024)

Binding between Cu2+/Zn2+ and aged polyethylene and polyethylene terephthalate microplastics in swine wastewaters: Adsorption behavior, and mechanism insights - Mengyu Ma; Ruxin Han; Ruoqi Han; Defu Xu; Feihu Li (Environmental Pollution, 2024)

Facile synthesis of carbon black and sodium alginate based particles system for efficient solar desalination of highly concentrated brine - Jiwen Zhang; Xiaozhen Hu; Kaiyuan Shi; Haiyan Sun; Dejian Yang; Mutian Yang; Bo Xu; Zhengwen Xu; Defu Xu (Journal of Environmental Chemical Engineering, 2024)

Injectable NGF-loaded double crosslinked collagen/hyaluronic acid hydrogels for irregular bone defect repair via neuro-guided osteogenic process - Qingsong Jiang; Liaomin Zhou; Yi Yang; Hu Long; Liming Ge; Defu Li; Changdao Mu; Wenli Lai; Zhilang Xu; Yan Wang (Chemical Engineering Journal, 2024)

Soil-dwelling grub larvae of Protaetia brevitarsis biodegrade polystyrene: Responses of gut microbiome and host metabolism - Jie Jiang; Haowen Xu; Xiaomu Cao; Yuqing Liang; Aoyun Mo; Xuelong Cao; Yan Liu; Mark Eric Benbow; Craig S. Criddle; Wei-Min Wu; Defu He (Science of The Total Environment, 2024)

Characteristic of geopolymer modified by MgO and its adsorption capacity of phosphate and ammonium ions from swine wastewater - Shuaishuai Li; Defu Xu; Die Wu; Alan Howard (Process Safety and Environmental Protection, 2024)

Enhanced removal efficiency of nitrogen and phosphorus from swine wastewater using MgO modified pig manure biochar - Liuying Wu; Defu Xu; Bing Li; Die Wu; Hong Yang (Journal of Environmental Chemical Engineering, 2024)

Preparation of a coagulant of polysilicate aluminum ferric from foundry dust and its coagulation performance in treatment of swine wastewater - Junhong Yi; Zanmei Chen; Defu Xu; Die Wu; Alan Howard (Journal of Cleaner Production, 2024)

Toxic effects of environmentally persistent free radicals (EPFRs) on the surface of tire wear particles on freshwater biofilms: The alleviating role after sewage-incubation-aging - Kun Li; Deyue Kong; Xiaojia Xiu; Wanqi Hao; Defu Xu (Chemosphere, 2023)

Treatment of steel industry wastewater by Poly-Aluminum-Ferric-Silicate coagulant prepared from coal gasification ash - Junhong Yi; Defu Xu; Die Wu; Hua Fang; Hong Yang (Colloids and Surfaces C: Environmental Aspects, 2023)

Risk factors of vestibular migraine-related brain white matter lesions - Yu Shen; Defu Li; Qian Cao; Mengyao Hu; Zhou Hou; Lijun Xu; Yanping Li; Daojun Hong (Acta Neurologica Belgica, 2023)

Variable drivers of surface turbulence under condition of stratified density currents in a tributary bay of Three Gorges Reservoir - Lianghong Long; Hui Xu; Meng Yan; Xia Yang; Xingxing Zhao; Daobin Ji; Yujie Cui; Zhongyong Yang; Defu Liu; Zhengjian Yang (Journal of Hydrology, 2023)

Dual-drug loaded polysaccharide-based self-healing hydrogels with multifunctionality for promoting diabetic wound healing - Weiwei Tan; Tao Long; Yanzhuo Wan; Bingchen Li; Zhilang Xu; Lei Zhao; Changdao Mu; Liming Ge; Defu Li (Carbohydrate Polymers, 2023)

Synthesis of NaA zeolite from foundry dust and its adsorption capacity of ammonia - Mengqing Wang; Defu Xu; Hui Ma; Bing Li; Alan Howard (Journal of Environmental Management, 2023)

Nutrient released characteristics of struvite-biochar fertilizer produced from concentrated sludge supernatant by fluidized bed reactor - Yingxue Li; Defu Xu; Haizhi Lin; Wenhua Wang; Hong Yang (Journal of Environmental Management, 2023)

Decontamination of multiple pollutants from eutrophic river water using iron-modification carbon/zeolite - Hui Ma; Yingxue Li; Defu Xu; Hanxin Tian; Hong Yang (Journal of Soils and Sediments, 2022)

Responses of nitrogen transformation and dissolved oxygen in constructed wetland to biochar and earthworm amendment - Lei Zhou; Jiajun Wang; Defu Xu; Yingxue Li; Bin Yao; Alan Howard (Environmental Science and Pollution Research, 2020)

Comparative study of carboxylic acid adsorption on calcite: l-malic acid, d-malic acid and succinic acid - Zhenxuan Li; Jiangtian Xiao; Lidong Huang; Defu Xu; Dagang Liu; Xiaowen Sun; Luji Yu; Hongsheng Wu (Carbonates and Evaporites, 2019)

Effect of earthworm and loach on Typha augustifolia aboveground and root litter residue in an integrated vertical subsurface flow constructed wetland - Yingxue Li; Defu Xu; Dongqin Zhou; Lei Zhou; Alan Howard (Wetlands Ecology and Management, 2019)

Regulatory Roles of Peroxisomal Metabolic Pathways Involved in Musk Secretion in Muskrats - Meishan Zhang; Shuang Yang; Minghui Shi; Shumiao Zhang; Tianxiang Zhang; Yimeng Li; Shanghua Xu; Muha Cha; Yuping Meng; Shaobi Lin; Juan Yu; Xuxin Li; et al. (The Journal of Membrane Biology, 2019)

Comparative study of the physicochemical and photocatalytic properties of water-soluble polymer-capped TiO2 nanoparticles - Jinfeng Lei; Lei Deng; Xinying Li; Yongbin Xu; Defu Li; Changdao Mu (Environmental Science and Pollution Research, 2018)

Isolation, Immobilization, and Degradation Performance of the 17β-Estradiol-Degrading Bacterium Rhodococcus sp. JX-2 - Jingxian Liu; Juan Liu; Defu Xu; Wanting Ling; Shunyao Li; Mindong Chen (Water, Air, & Soil Pollution, 2016)

Chronic Exposure to Perfluorooctane Sulfonate Reduces Lifespan of Caenorhabditis elegans Through Insulin/IGF-1 Signaling - Tiantian Xu; Ping Li; Siyu Wu; Dan Li; Jingxuan Wu; Kathleen M. Raley-Susman; Defu He (Bulletin of Environmental Contamination and Toxicology, 2016)

Impacts of low-molecular-weight organic acids on aquatic behavior of graphene nanoplatelets and their induced algal toxicity and antioxidant capacity - Zhuang Wang; Yucheng Gao; Se Wang; Hao Fang; Defu Xu; Fan Zhang (Environmental Science and Pollution Research, 2016)

Purifying capability, enzyme activity, and nitrification potentials in December in integrated vertical flow constructed wetland with earthworms and different substrates - Defu Xu; Jiaru Gu; Yingxue Li; Yu Zhang; Alan Howard; Yidong Guan; Jiuhai Li; Hui Xu (Environmental Science and Pollution Research, 2016)

Performance investigation of SP3 and diffusion approximation for three-dimensional whole-body optical imaging of small animals - Defu Yang; Xueli Chen; Xu Cao; Jing Wang; Jimin Liang; Jie Tian (Medical & Biological Engineering & Computing, 2015)

Influence of UV radiation on chlorophyll, and antioxidant enzymes of wetland plants in different types of constructed wetland - Defu Xu; Yinjuan Wu; Yingxue Li; Alan Howard; Xiaodong Jiang; Yidong Guan; Yongxia Gao (Environmental Science and Pollution Research, 2014)

Influence of earthworm Eisenia fetida on removal efficiency of N and P in vertical flow constructed wetland - Defu Xu; Yingxue Li; Alan Howard (Environmental Science and Pollution Research, 2013)

Effect of Iron Plaque Formation on Phosphorus Accumulation and Availability in the Rhizosphere of Wetland Plants - Defu Xu; Jianming Xu; Yan He; P. M. Huang (Water, Air, & Soil Pollution, 2009)

A preliminary study of trace elements in plasma protein by gel chromatography combined with SXRF - Nianqing Liu; Plngsheng Liu; Kongjiang Wamg; Defu Chen; Jinyuan Zhao; Qing Xu (Biological Trace Element Research, 1999)